The phenotypic appearance of Japanese persimmon (Diospyros kaki L.f.) in Karo District, North Sumatra, Indonesia - DIANA SOFIA HANAFIAH; SEPTIAS SANGGITA; KHAIRUNNISA LUBIS (Society for Indonesian Biodiversity, 2018)
Hanafiah DS, Sanggita S, Lubis K. 2018. The phenotypic appearance of Japanese persimmon (Diospyros kaki L.f.) in Karo District, North Sumatra, Indonesia. Biodiversitas 19: 559-564. The farmers in Karo District began to be less interested in cultivating kesemek or Japanese persimmon (Diospyros kaki L.f.). Due to the price of this commodity has dropped in the market, the farmers cut down the tree and cultivate more favorable horticultural crops, such as vegetable and citrus cultivation. It is necessary to conduct a study to obtained sufficient information to determine the necessary steps in order to preserve Japanese persimmon plants in Karo District. One first steps was to get information of accession characteristic of Japanese persimmon in Karo District. This research aimed to identify relationships of morphological characteristics among individuals of Japanese persimmon plants. The research was conducted from May until July 2017 at Berastagi, Merdeka, Kabanjahe, and Dolat Rayat sub-districts of Karo District, North Sumatra, Indonesia. The survey method using Japanese persimmon descriptor of Diospyros kaki L.f. by the International Union for the Protection of New Varieties (UPOV) with the purposive method for location determination and technique sampling. Thirty-six accessions of Japanese persimmon plants were studied. Based on clustering method of the morphological characteristic, 4 clusters are formed. This difference was canopy form, leaf shape and fruit morphological. Accession 34 from Dolat Rayat Distict has different fruit characters with other accessions.